Success Factors for Clean Development Mechanism Implementation in Malaysia (Issues in Social and Environmental Accounting (ISEA), 2013)
The Clean Development Mechanism (CDM), established under the Kyoto Protocol, is one of the market-based mechanisms developed to assist industrialized countries mitigate greenhouse gas (GHG) emissions, achieve emission reduction targets, and at the same time promote sustainable development in developing countries. The CDM, which provides flexibility and costeffectiveness in meeting GHG emission reduction targets, has captured interest globally. CDM implementation is expected to generate benefits, give developing countries a sense of ownership, and share the global load in tackling global warming and climate change. However, CDM implementation faces several complications. The successful participation of developing countries in emission reduction projects presents ongoing challenges, which inhibit their drive towards sustainable development goals. Through a comprehensive review of the literature and theoretical analysis, several factors have been identified as significant to successful CDM implementation in Malaysia. These success factors, which include regulation and a legal framework, competitive advantage, green supply chain, ethical values, financial benefits, and technology transfer, are presented and the importance of each factor is discussed.